Warfarin-induced toxic epidermal necrolysis after mitral valve replacement. (November 2020) - Kuroda, Taiyo; Yokoyama, Yukifusa; Yamada, Masao; Yuhara, Satoshi; Hasegawa, Hiroki; Yokote, Jun
Stevens-Johnson syndrome and toxic epidermal necrolysis are rare diseases that cause acute destruction of the epithelium of the skin and mucous membranes, almost always attributable to drugs. However, warfarin-induced Stevens-Johnson syndrome and toxic epidermal necrolysis is extremely rare. We report the case of 71-year-old woman who died due to destructive erosion all over her skin and mucous membranes. She had received a mitral valve prosthesis, and warfarin was prescribed for antithrombotic therapy. A lymphocyte transformation test for drug hypersensitivity and the clinical history confirmed this phenomenon as warfarin-induced toxic epidermal necrolysis.